(untitled) (Journal of Applied Learning and Teaching, 2025)
The COVID-19 pandemic has had a profound and lasting impact on education, with change and consequences that extend beyond its duration. The emergency remote teaching (ERT), the sudden shift from face-to-face to online instruction, left many educators worldwide unprepared. While cases of ERT abound, existing literature focuses primarily on ERT in the classroom setting. There is also a paucity of studies exploring the longer-term impact of ERT on the educational landscape. This case study interrogates how educators in the context of Hong Kong higher education navigated and advanced teaching beyond the classroom during ERT. It further explores the transition and lasting impact of pandemic-implicated educational practices. As diversity is the primacy underlying the case study approach (Stake, 1995), four cases were selected based on various disciplines, technologies, and pandemic-implicated educational practices in Hong Kong. The findings reveal that these pandemic-implicated practices do not simply revert to the normal after the pandemic, which was the original face-to-face instruction. Instead, they evolve into blended learning practices at various levels, including activity-level blending, course-level blending, and programme-level blending. The paper concludes by discussing the pedagogical implications of the “new normal” when blended learning becomes a prevalent form of teaching.